Jahrbuch für Kulturpolitik 2017/18 Welt. Kultur. Politik. - Kulturpolitik in Zeiten der Globalisierung - Blumenreich, Ulrike; Dengel, Sabine; Hippe, Wolfgang; Sievers, Norbert (Jahrbuch für Kulturpolitik, 2018)
The 2017 Yearbook of Cultural Politics focuses on the challenges of cultural politics in times of progressing globalization.